Delay spread estimation in 4,2GHz band using game ray based method (2016)
The evolution of mobile systems has leaded to new frequency attributions like 3,5 to 4,2 GHz band. In this paper, we show the channel behavior of 4,2GHz in indoor scenario using a ray based system and compare delay spread results with measurements. We try to tune our model, adjusting permittivity values to reduce the mean standard error and analyze the effect of the permittivity differences in the scenario. © 2016 IEEE.